The Role of Islamic Religious Education Teachers in Guiding Learners to Overcome Difficulties in Reading the Qur'an - Yuli Ana Sadin; Muh. Arif; Muhammad Zainul Arifin; Abd.Wahid (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in guiding students to overcome difficulties in reading the Qur'an at SDN 12 Wonosari, the methods used by the teachers, as well as the supporting and inhibiting factors in the guidance process. This research uses a descriptive qualitative approach with data collection techniques thru observation, interviews, and documentation. The research informants consist of the school principal, PAI teachers, and fifth-grade students who have difficulty reading the Qur'an. Data were analyzed using the Miles and Huberman model thru data reduction, data presentation, and conclusion drawing. The research results show that PAI teachers play the role of guides, motivators, and evaluators in helping students overcome difficulties in reading the Qur'an thru individual guidance, providing correct reading examples, correcting mistakes, and motivating learning. The methods used include the talaqqi/musyafahah method, the tartil method, and an individual approach tailored to the students' abilities. Supporting factors include student motivation, parental support, availability of facilities, and cooperation from the school. As for the inhibiting factors, they include differences in students' basic abilities, limited learning time, low interest in studying, and lack of practice at home. This study concludes that the active role of PAI teachers is very important in improving students' ability to read the Qur'an. Thru the use of appropriate methods and support from various parties, difficulties in reading the Qur'an can be gradually overcome, enabling students to read the Qur'an better and more fluently.